PEMANFAATAN TEKNOLOGI INTERNET MENGGUNAKAN MEDIA SOSIAL SEBAGAI SARANA PENYEBARAN INFORMASI DAN PROMOSI PADA MIN 18 JAKARTA - Lady Diana Warpindyastuti; Meiva Eka Sri Sulistyawati (Universitas Bina Sarana Informatika, 2018)
The development of internet technology is so rapidly today many gave birth to various types of social media. Social media is becoming very popular because it provides easiness in communication. In terms of marketing activities, social media applications have an important role, especially in the dissemination of information and promotion. In addition to easier, do marketing through social media applications faster and cheaper. In this research case study was conducted at MIN 18 Jakarta. The study used descriptive-qualitative method, where this method describes the phenomena that exist in accordance with the current state of research. Social media is very useful for schools, this application is very useful in the dissemination of information and promotion. The development of internet technology that also impact on the development of social media is quite well utilized by MIN 18 Jakarta as a means of dissemination of information and promotion.